Eksistensi Pondok Pesantren Syahamah Putri Dalam Menjaga Paham Ahlusunah Waljamaah di Kecamatan Margoyoso Kabupaten Pati Provinsi Jawa Tengah - Rahmawarni Harahap; Hasan Bakti Nasution; Mohammad Al Farabi (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
This study aims to analyze the curriculum, kiai and teacher strategies, and describe the contribution of Pondok Pesantren Syahamah Pati Putri in maintaining the understanding of Ahlusunah Waljamaah to the community in Margoyoso sub-district, Pati district, Central Java province. This research was conducted using field research method with qualitative approach. Research instruments through observation, interviews and document studies. The data sources of this research are primary and secondary data sources obtained from Syahamah Pati Putri Islamic Boarding School in Margoyoso sub-district, Pati district, Central Java province. The results showed that the curriculum applied at Syahamah Pati Putri Islamic Boarding School adheres to the salaf manhaj by being guided by the turats books which include religious science and Arabic language materials, such as tawhid, fiqh, morals / Sufism, nahu, saraf, and Al-Qur'an. The strategy of the kiai/leader of the hut in maintaining Ahlusunah Waljamaah understanding is to equip students with "Rudud" book material, strengthening Arabic, memorizing the Qur'an and holding daurah, limiting the use of information technology, implementing traditions and values of Ahlusunah Waljamaah; recitation of dhikr, yasinan, maulidan, hadlrah, pilgrimage to the grave of the guardian, instilling disciplinary and moral values; faith in Allah and His Messenger, enthusiasm for learning and practicing and teaching, maintaining good manners, not taking other people's rights without permission, not speaking without knowledge. The teacher's strategy is to teach the basics of creed to students, warn students from views that deviate from Ahlusunah Waljamaah, introduce leaders or figures of Ahlusunah Waljamaah, muraja'ah lessons, and record lessons. The contribution of Pondok Pesantren Syahamah Pati Putri in maintaining the understanding of Ahlusunah Waljamaah in Margoyoso District is that the ustadz hold routine studies for the community once a week and alumni who have taught in many pesantren and made Ahlusunah Waljamaah assemblies in various provinces in Indonesia.